Tailoring Teaching Instructions According to Student’s Different Learning Styles: Are We Hitting the Right Button? - Chew, Keng Sheng (2016)
To address the diverse preferred learning styles, one of the oft-cited recommendations for educatorsis to tailor teaching instructions accordingly. This pedagogy however, lacks scientific evidences.Furthermore, in medical curriculum, tailoring instructions according to preferred learning styles isnot pragmatic. This is because different subjects and in different settings matter may be best deliveredin specific delivery mode. Furthermore, patients’ presentations are often multi-sensorial. As such, theonus is on the students themselves to adjust the amount of learning efforts they put in according totheir preferred or not preferred learning styles.